How Mitochondrial DNA Can Write Pre-History: Kinship and Culture in Duero Basin (Spain) during Chalcolithic and Bronze Age - Sara Palomo-Díez; Ángel Esparza-Arroyo; Olga Rickards; Cristina Martínez-Labarga; Eduardo Arroyo-Pardo (Genealogy, 2023)
The chronological period from the beginning of the Chalcolithic Age to the end of the Bronze Age on the Iberian northern sub-plateau of the Iberic Peninsula involves interesting social and cultural phenomena, such as the appearance of the Bell Beaker and, later, the Cogotas I cultures. This work constructs a genetic characterisation of the maternal lineages of the human population that lived on the northern sub-plateau between 5000 and 3000 years ago through an analysis of mitochondrial DNA (mtDNA), a kind of genetic marker that is inherited through maternal lineages, unaltered from generation to generation. Population and cultural questions are investigated through mtDNA analyses. This study intends to shed light on the following questions. Were individuals who were buried together in multiple or collective burials biologically related through their maternal lineages? Were there distinct maternal human lineages in the same or different geographical areas if different material cultures (Bell Beaker and Cogotas I) were associated with the arrival of new human populations who established close biological relationships with the endogenous populations? Or could this be the result of the transmission of knowledge without human populations mixing? Another important question is whether the material cultures were related to the female populations. We analysed 91 individuals from 28 different archaeological sites of the Iberian northern sub-plateau from four different chrono-cultural periods (Pre-Bell Beaker, Bell Beaker, Proto-Cogotas I, and Cogotas I), from the end of the Chalcolithic Age up to the Bronze Age. There were two historical moments of new populations arriving: the first during the Pre-Bell Beaker period, associated with the K mtDNA haplogroup, and the second during the Proto-Cogotas I culture, with new lineages of the H, HVO, and T haplogroups. Neither of these new population flows were directly associated with the maximum development of the two main material cultures Bell Beaker and Cogotas I, so they must have occurred immediately beforehand, during the Pre-Bell Beaker and Proto-Cogotas I periods, respectively. However, we cannot discard an association between the populations and material cultures. Curiously, it has also been observed that there was also a tendency towards multiple burials, in which the individuals who were buried together belonged to the same maternal lineage, during these two periods of population change. This study has shed some light on the populational changes that occurred through these different periods in this specific geographical area of the northern sub-plateau of the Iberian Peninsula.